Evaluation of Return on Social Media Investment with A Critical Look Over Its Non-Financial Aspect - Behzad Feizi Oskooei , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The dot-com bubble of 1995-2002 allowed the internet to become a viable marketing tool. Marketers changed their approach to the market and customers became the center of thinking; being online presence turned into a priority. The introduction of web 2.0 opened a new door and changed the ways companies, communities, and other users interact with each other. Marketers recognized the importance of content marketing: more value is added to customers, and their needs and business models change from old school models to new strategies. Every day more and more global companies use social media, some companies have realized the importance of it, and because they know it works, others because they are afraid to go out of business through these changes. Measuring the effectiveness of social media or return on investment (ROI) is a key factor in the long-term and short-term success of SM marketing and management programs. The purpose of this study is how to deepen and broaden the knowledge of the social media return of investment by dividing it into two major parts: a theoretical section and a practical process. In the first part, I will discuss social media, consumer behaviors, media engagement format, and marketing and social marketing funnels, the ROI definition. The second section will be the methodology part, in which I will discuss how to calculate ROI and why different companies have different definitions of return of investment by step-by-step analyzing a case study.